2015
DOI: 10.1007/s00062-015-0422-y
|View full text |Cite
|
Sign up to set email alerts
|

Some Remarks on Imaging of the Inner Ear: Options and Limitations

Abstract: The temporal bone has a highly complex anatomical structure, in which the sensory organs of the cochlea and the vestibular system are contained within a small space together with the sound-conducting system of the middle ear. Detailed imaging is thus required in this anatomical area. There are a great many clinical aims for which the highest-possible spatial resolution is required. These include the localization of cerebrospinal fluid fistulas, the detection of malformations of the middle and inner ear and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
16
0
3
Order By: Relevance
“…The pathogenesis of perilymph fistulas is thought to be the result of a direct communication between the subarachnoid space and inner ear caused by a defect in the bony partition of the fundus of the IAC [14, 15] (not identifiable with studies of images or other methods) or enlarged cochlear or vestibular aqueduct [13, 16, 32]. For a long time, EVA was considered as the main cause of the presence of intraoperative CSF leak [63, 64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of perilymph fistulas is thought to be the result of a direct communication between the subarachnoid space and inner ear caused by a defect in the bony partition of the fundus of the IAC [14, 15] (not identifiable with studies of images or other methods) or enlarged cochlear or vestibular aqueduct [13, 16, 32]. For a long time, EVA was considered as the main cause of the presence of intraoperative CSF leak [63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, different for the ECA and EVA studies; these can easily be conducted radiologically by means of current CT methods. Evaluating the conditions of these aqueducts which can provoke CSF leak may be particularly useful in planning cochlear implantation surgery, stapedectomy, and others (Figure 1) [16]. …”
Section: Introductionmentioning
confidence: 99%
“…CT can detect signs of perilymphatic fistulae (i.e. pneumolabyrinth) but fails to detect subtle traumatic lesions within the inner ear, such as labyrinthine haemorrhage or axonal damage along central auditory pathways (9). Many anatomic structures of the middle and inner ears are not optimally depicted using conventional CT with image reconstruction in the standard axial and coronal planes.…”
Section: Ctmentioning
confidence: 99%
“…Rated as: -= not visible, += poorly, ++= moderately and +++= good visible. (6) (54) visualization of the cochlear partitioning (9). A recent paper by Maillot et al (12) indicated that MDCT allows radiologists to examine the complex anatomy of the temporal bone with sub-millimeter resolution and is the first modality of choice.…”
Section: Ctmentioning
confidence: 99%
See 1 more Smart Citation